2009
DOI: 10.1021/jp809561p
|View full text |Cite
|
Sign up to set email alerts
|

A Green Chemistry Approach for the Synthesis of Flower-like Ag-Doped MnO2 Nanostructures Probed by Surface-Enhanced Raman Spectroscopy

Abstract: Novel hierarchical flower-like nanostructures of Ag-doped MnO 2 have been obtained by facile wet chemical and photochemical routes. UV-visible absorption spectroscopy measurement reveals that doping of Ag nanoparticles in MnO 2 nanostructures leads to a red shift of the absorption edge and reduces the optical band gap energy from 2.68 to 2.51 eV while compared with undoped MnO 2 . Raman study reveals that the band broadens and shifts toward higher wavenumbers as the MnO 6 octahedron is contorted by Ag doping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 79 publications
3
57
0
Order By: Relevance
“…Second, the large surface area of TiN NRs is conductive for adsorbing sufficient analyte molecules. Third, the value of optical band gap (E g ) of TiN-900 NRs is estimated by a classical Tauc approach [26]. The E g value of the TiN-900 NRs is about 2.25 eV, which is lower than that of exciting source (ca.…”
Section: Sers Property Of Tin Nrsmentioning
confidence: 98%
“…Second, the large surface area of TiN NRs is conductive for adsorbing sufficient analyte molecules. Third, the value of optical band gap (E g ) of TiN-900 NRs is estimated by a classical Tauc approach [26]. The E g value of the TiN-900 NRs is about 2.25 eV, which is lower than that of exciting source (ca.…”
Section: Sers Property Of Tin Nrsmentioning
confidence: 98%
“…In summary, the morphologies of ZnO were influenced by the basicity. During processing, the Zn 2+ ions were transformed by OH -to form zinc hydroxide species: Zn(OH) 2 , Zn(OH) 3 − and Zn(OH) 4 2− controlled by pH and [Zn 2+ ] concentration [30]. Some Zn 2+ ions were also left in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Thus they have been attracted interest a number of scientists and engineers. The properties and performance of micro-and nanostructure materials are largely influenced by the morphologies comparing with their bulk counterparts [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…10 Many newly derived performances and functions of manganese dioxide have been explored by doping of flexible ions, such as Al, Ni, Co, Cr, Fe and Li, resulting in continually broadening applications. [11][12][13][14][15][16][17] Jana et al 16 reported the synthesis of flower-like Ag doped MnO 2 ; they implied that a red shift in the optical response and a concomitant reduction of the band gap energy were observed after the incorporation of Ag into MnO 2 . Yu 17 and co-workers reported the effects of metal ions Fe 3z and Al 3z on the structures, morphologies and electrochemical properties of MnO 2 , and their analysis also showed that the addition of Fe 3z and Al 3z affected the hydrothermal growth of MnO 2 by changing the chemical potential of the solution.…”
Section: Introductionmentioning
confidence: 99%